Representaciones semióticas en números racionales - Granados Niño, Nancy Johana (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: This research had as purpose to analyze the semiotic representations that students use conceptualizing rational numbers, it was carried out with 18 students from seventh grade of a private school in Tunja (Boyacá) where difficulty in conceptualization of rational numbers is evidenced, according to the representations they remember, they do not find a relation between one interpretation and the other. It means they do not find the adequate semiosis to achieve the noesis (Duval, 2006), generating obstacles and difficulties in the learning of the mathematical object. The study followed a qualitative interpretive approach, directed from action research, working on the spiral of Kemmis and Carr (1983). It constitutes the cycle with the planning, acting, observing and reflecting phases. The theory on which the study was based is Duval's (2004), where the three cognitive activities related to semiosis were observed, described and interpreted, which are: presence of semiotic representation, treatment and conversion. The results obtained show that the semiotic representation register used the most by the students corresponds to the graphic scheme where the representation in the form of a cake predominates from the part-whole meaning of the unit, an interpretation that generated obstacles and artificiality in the conceptualization. Moreover, treatments are established connecting the arithmetic register and conversions between the common language registers, arithmetic and graphs.